전문수기마사지 동작 중 원형강찰법에 대한 동작 및 가압력 분석 - 김영호; 유제성; 손종상; 황선홍; 손량희; 차인혁; 송재훈; 송성재; Kim, Y.H; Ryu, J.S; Son, J.S; Hwang, S.H; et al. (Journal of biomedical engineering research, 2010)
In this study, the circular friction massage technique was performed on the trapezius, the levator scapulae, and the deltoid muscles to collect the information on massage pressures and positions, and thus to utilize it in professional massage system design. Massage motion was measured with the 3-D motion capture system and finger pressures were simultaneously obtained with grip sensors. Massage motions, pressure patterns, and pressure times were different on each muscle, and the motion trajectory was similar to the ellipsoidal shape. The trapezius had higher pressure, longer massage time, and larger impulse than other muscles. These results could be useful to design a massage system based on biomechanical analysis. In order to improve massage effect, it is also strongly recommended that the tip of the system be similar with that of a human thumb in shape and material.